2020
DOI: 10.2139/ssrn.3750684
|View full text |Cite
|
Sign up to set email alerts
|

Social Assimilation and Labor Market Outcomes of Migrants in China

Abstract: The CENTER FOR DEVELOPMENT RESEARCH (ZEF) was established in 1995 as an international, interdisciplinary research institute at the University of Bonn. Research and teaching at ZEF address political, economic and ecological development problems. ZEF closely cooperates with national and international partners in research and development organizations. For information, see: www.zef.de. ZEF Discussion Papers on Development Policy are intended to stimulate discussion among researchers, practitioners and policy make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
(29 reference statements)
1
7
1
Order By: Relevance
“…These results suggest that the level of assimilation plays an important role not only in obtaining employment but on the characteristics of the job as well, especially in terms of the reduction in the incidence of overeducation. Our results are in line with those in Constant and Zimmermann (2008) and Cai and Zimmermann (2020) though they are contrary to those found by Gorinas (2014), Casey and Dustmann (2010) and Nekby and Rodin (2010).…”
Section: Full Samplesupporting
confidence: 84%
See 2 more Smart Citations
“…These results suggest that the level of assimilation plays an important role not only in obtaining employment but on the characteristics of the job as well, especially in terms of the reduction in the incidence of overeducation. Our results are in line with those in Constant and Zimmermann (2008) and Cai and Zimmermann (2020) though they are contrary to those found by Gorinas (2014), Casey and Dustmann (2010) and Nekby and Rodin (2010).…”
Section: Full Samplesupporting
confidence: 84%
“…For instance, Carillo et al (2021) use Italian data and show that ethnic identity has a significant positive affect on the probability of finding employment. Similarly, using Chinese internal migration data, Cai and Zimmermann (2020) find a positive and significant impact of assimilation on hourly wages, and assimilation also reduces the number of hours worked. However, Islam and Raschky (2015), using Canadian data, find a negligible effect of assimilation on immigrants' labour market outcomes.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…For instance, Carillo et al (2021) use Italian data and show that ethnic identity has a significant positive effect on the probability of finding employment. Similarly, using Chinese internal migration data, Cai and Zimmermann (2020) find a positive and significant impact of assimilation on hourly wages, and assimilation also reduces the number of hours worked. However, Islam and Raschky (2015), using Canadian data, find a negligible effect of assimilation on immigrants' labour market outcomes.…”
Section: Introductionmentioning
confidence: 87%
“…Recent literature has shown that ethnic identity/social assimilation plays an important role in the economic outcomes of immigrants (Constant and Zimmermann, 2008;Battu and Zenou, 2010;Bisin et al, 2011;Cai and Zimmermann, 2020;Carillo et al, 2021). However, there is no consensus in the studies as the results are highly dependent on the type of country under study and the type of data available to determine an immigrant's ethnic identity.…”
Section: Introductionmentioning
confidence: 99%